Genetics and orofacial clefts: a clinical perspective - Kini, U (Springer Nature, 2023)
Orofacial clefts (OFCs) are the most common congenital craniofacial anomaly seen in humans. Most OFCs are sporadic and isolated - these are thought to be multifactorial in origin. Chromosomal and monogenic variants account for the syndromic forms and for some of the non-syndromic inherited forms. This review discusses the importance of genetic testing and the current clinical strategy to deliver a genomics service that is of direct benefit to patients and their families.